The use of a flow field correction technique for alleviating the North Atlantic cold bias with application to the Kiel Climate Model - Drews, Annika; Greatbatch, Richard John; Ding, Hui; Latif, Mojib; Park, Wonsun (Ocean Dynamics, 2015)
The North Atlantic cold bias, associated with the misplacement of the North Atlantic Current (NAC) and typically extending from the surface to 1000 m depth, is a common problem in coupled models that compromises model fidelity. We investigate the use of a flow field correction (FFC) to adjust the path of the NAC and alleviate the cold bias. The FFC consists of three steps. First, climatological potential temperature (T) and salinity (S) fields for use with the model are produced using a three-dimensional restoring technique. Second, these T, S fields are used to modify the momentum equations of the ocean model. In the third stage, the correction term is diagnosed to construct a flow-independent correction. Results using the Kiel Climate Model show that the FFC allows the establishment of a northwest corner, substantially alleviating the subsurface cold bias. A cold bias remains at the surface but can be eliminated by additionally correcting the surface freshwater flux, without adjusting the surface heat flux seen by the ocean model. A model version in which only the surface fluxes of heat and freshwater are corrected continues to exhibit the incorrect path of the NAC and a strong subsurface bias. We also show that the bias in the atmospheric circulation is reduced in some corrected model versions. The FFC can be regarded as a way to correct for model error, e.g. associated with the deep water mass pathways and their impact on the large-scale ocean circulation, and unresolved processes such as eddy momentum flux convergence.